1999
DOI: 10.1136/jnnp.67.4.481
|View full text |Cite
|
Sign up to set email alerts
|

Sound lateralisation in patients with left or right cerebral hemispheric lesions: relation with unilateral visuospatial neglect

Abstract: Objectives-To localise the brain lesion that causes disturbances of sound lateralisation and to examine the correlation between such deficit and unilateral visuospatial neglect. Method-There were 29 patients with right brain damage, 15 patients with left brain damage, and 22 healthy controls, who had normal auditory and binaural thresholds. A device was used that delivered sound to the left and right ears with an interaural time diVerence using headphones. The amplitude (an index of ability to detect sound ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
29
2
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 15 publications
8
29
2
3
Order By: Relevance
“…Several studies reported mis-localization within the hemispace contralateral to the brain lesion, after right or left hemispheric lesions (Wortis and Pfeffer 1948;Sanchez-Longo and Forster 1958;Klingon and Bontecou 1966;Poirier et al 1994;Zatorre et al 1995). Other studies described deficits within the whole field following unilateral lesions (Haeske-Dewick et al 1996;Zatorre and Penhune 2001) and some advocated either right (Ruff et al 1981;Bisiach et al 1984;Tanaka et al 1999) or left (Pinek et al 1989) hemispheric specialization for auditory localization. While some authors attributed impaired sound localization exclusively to lesions in temporal lobe (Sanchez-Longo and Forster 1958;Efron et al 1983;Zatorre and Penhune 2001), others questioned its importance in sound localization (Jerger et al 1972) or reported auditory spatial deficits following parietal lobe lesions (Bisiach et al 1984;Pinek and Brouchon 1992;Griffiths et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported mis-localization within the hemispace contralateral to the brain lesion, after right or left hemispheric lesions (Wortis and Pfeffer 1948;Sanchez-Longo and Forster 1958;Klingon and Bontecou 1966;Poirier et al 1994;Zatorre et al 1995). Other studies described deficits within the whole field following unilateral lesions (Haeske-Dewick et al 1996;Zatorre and Penhune 2001) and some advocated either right (Ruff et al 1981;Bisiach et al 1984;Tanaka et al 1999) or left (Pinek et al 1989) hemispheric specialization for auditory localization. While some authors attributed impaired sound localization exclusively to lesions in temporal lobe (Sanchez-Longo and Forster 1958;Efron et al 1983;Zatorre and Penhune 2001), others questioned its importance in sound localization (Jerger et al 1972) or reported auditory spatial deficits following parietal lobe lesions (Bisiach et al 1984;Pinek and Brouchon 1992;Griffiths et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported mislocalization within the hemispace contralateral to the brain lesion, after right or left hemispheric lesions (Wortis and Pfeffer, 1948;Sanchez-Longo and Forster, 1958;Klingon and Bontecou, 1966;Poirier et al, 1994;Zatorre et al, 1995). Other studies described deficits within the whole field following unilateral lesions (Haeske-Dewick et al, 1996;Zatorre and Penhune, 2001) and some advocated either right (Ruff et al, 1981;Bisiach et al, 1984;Tanaka et al, 1999) or left (Pinek et al, 1989) hemispheric specialization for auditory localization.…”
Section: Introductionmentioning
confidence: 99%
“…Ainda, na mesma literatura especializada, a média de idade encontrada para os pacientes com lesão foi: 61 e 63 anos (De Renzi et al, 1989), 36 anos (Obert e Cranford, 1990), 64 anos (Robertson et al, 1997), 56 anos Discussão (Tanaka et al, 1999), 58 anos (Deouell et al, 2000), 63 anos (Bamiou et al, 2006), 40, 53 e 55 anos (Biedermann et al, 2008), 67 e 73 anos (Gopinath et al, 2009). Pudemos verificar que a maioria destes estudos mostrou média de idade acima de 40 anos, desta forma, a presente pesquisa apresentou média de idade semelhante àquela encontrada pela literatura especializada.…”
Section: Parte IV -Discussão Sobre a Caracterização Dos Resultados Daunclassified
“…(Bisiach et al, 1984, Kileny et al, 1987, Obert e Cranford, 1990, Tanaka et al, 1999, Deouell et al, 2000, Bellmann et al, 2001, Adriani et al, 2003, Alvarenga et al, 2005, Bamiou et al, 2006, Biedermann et al, 2008, Gopinath et al, 2009). …”
Section: Parte IV -Discussão Sobre a Caracterização Dos Resultados Damentioning
confidence: 99%
See 1 more Smart Citation